Antecedents of Self Mental Driving Agility on Employee Performance at Social Security Administrative Body for Health (BPJS Kesehatan) Sumatera Utara and Aceh Regional - Sari , Radiah Nazmah; ., Sirojuzilam; Siahaan, Elisabet; Absah, Yeni (Journal of Ecohumanism, 2025)
Background of this study is the still low readiness of BPJS Kesehatan employees to face change, which affects the achievement of organizational targets. The performance achievement in the human resources sector has not met the set target, indicating that the management of human resources has not been optimized and needs to be addressed immediately. Furthermore, the low passing rate of employees in the agility test illustrates that employees are not yet sufficiently responsive and adaptive to the changes occurring. The aim of this study is to analyze strategic steps in improving performance by enhancing employee readiness for change, organizational agility, and self-mental driving agility. The sampling technique used is census, involving all Assistant Managers at BPJS Kesehatan, Deputyship Region I, totaling 122 people. The results of this study are as follows: (1) Organizational agility has a positive but not significant effect on self-mental driving agility. (2) Employee agility has a positive and significant effect on self-mental driving agility. (3) Organizational agility has a positive and significant effect on employee readiness to change. (4) Employee agility has a positive but not significant effect on employee readiness to change. (5) Organizational agility has a positive but not significant effect on employee performance. (6) Employee agility has a positive and significant effect on employee performance. (7) Organizational agility has a positive but not significant effect on employee readiness to change through self-mental driving agility. (8) Employee agility has a positive and significant effect on employee readiness to change through self-mental driving agility. (9) Organizational agility has a positive but not significant effect on employee performance through self-mental driving agility. (10) Organizational agility has a positive and significant effect on employee performance through employee readiness to change. (11) Employee agility has a positive and significant effect on employee performance through self-mental driving agility. (12) Employee agility has a positive but not significant effect on employee performance through employee readiness to change.